PENDEKATAN DAKWAH LEMBAGA DAKWAH KAMPUS (LDK) AFDHALUL FIKRI STKIP PGRI SUMATERA BARAT - Hanafi, Beni Putra (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The background of this research originated from the writer's interest in the existence of Campus Da'wah Institutions in Public Higher Education, one of which is located in STKIP PGRI West Sumatra. According to the observations of the author LDK is quite developed among LDK in other public universities and Islamic universities. The problem examined by the researcher in this thesis is how the Campus Institution Da'wah Approach (LDK) Afdahalul Fikri (AF) STKIP PGRI West Sumatra. The limitation of the problem is how is the general description of LDK STKIP PGRI West Sumatra, how is the da'wah approach that LDK AF STKIP PGRI West Sumatra is doing to its da'wah partners and what method of propaganda is used by LDK STKIP PGRI West Sumatra.To find out the approach of Da'wah LDK AF STKIP PGRI West Sumatra, the writer uses a qualitative method with a descriptive approach. The qualitative method with a descriptive approach is a research method by looking at and describing facts that occur in the real field which are then used as data for writing. The facts - the writer gets by means of observation, interviews and documentation, after all the data the author gets the new author if the writing material that fits the limitations of the author's research.Based on the data found in the implementation of the research, the findings of this study are this LDK which was established on April 22, 1998 academics of STKIP PGRI West Sumatra, youth and communities outside the campus STKIP PGRI West Sumatra in order to recognize and empower their potential for personal benefit, the campus community and the wider community in general to realize the community of faith and that has the blessing of Allah SWT. This LDK has 6 departments that have their respective work programs.To realize the goals and work programs, this LDK approach - approach to preaching partners individually, this individual approach is an approach that is more focused on the psychological understanding of the missionary partner itself, so that the LDK board knows what messages and methods should be used in preaching against its cadres. In addition, this approach also further strengthens the ukhuwah between LDK administrators and propaganda cadres. The LDK method used in da'wah is by two methods, namely 1) the method of discussion by conducting trainings, seminars and general studies and annisa forums; 2) writing method by forming cadre bulletin, Mading, LDK FSI AF (Afdhalul Fikri Islamic Study Forum) and reading space.